Prevalence of childhood hearing loss and secular trends: a systematic review and meta-analysis - Wang, Jing; Sung, Valerie; Carew, Peter; Burt, Rachel A.; Liu, Mengjiao; Wang, Yichao; Afandi, Aflah; Wake, Melissa (Elsevier, 2019)
BACKGROUND: Better epidemiologic information on childhood hearing loss would inform research priorities and efforts to prevent its progression. OBJECTIVES: To estimate prevalence and secular trends in children’s hearing loss. DATA SOURCES: We searched MEDLINE and Embase from January 1996 to August 2017. STUDY ELIGIBILITY CRITERIA: We included epidemiologic studies in English reporting hearing loss prevalence. STUDY APPRAISAL AND SYNTHESIS METHODS: The modified Leboeuf-Yde and Lauritsen tool was used to assess methodological quality. Meta-analyses combined study-specific estimates using random-effects models. PARTICIPANTS: Children 0 to 18 years of age. RESULTS: Among 88 eligible studies, 43.2% included audiometric measurement of speech frequencies. In meta-analyses, pooled prevalence estimates of slight or worse bilateral speech frequency losses >15 decibels hearing level (dB HL) were 13.1% (95% confidence interval [CI], 10.0−17.0). Using progressively more stringent cutpoints, pooled prevalence estimates were 8.1% (95% CI, 1.3−19.8) with >20 dB HL, 2.2% (95% CI, 1.4−3.0) with >25 dB HL, 1.8% (95% CI, 0.4−4.1) with >30 dB HL, and 0.9% (95% CI, 0.1−2.6) with >40 dB HL. Also, 8.9% (95% CI, 6.4−12.3) had likely sensorineural losses >15 dB HL in 1 or both ears, and 1.2% (95% CI, 0.5−2.1) had self-reported hearing loss. From 1990 to 2010, the prevalence of losses >15 dB HL in 1 or both ears rose substantially (all P for trend <.001). LIMITATIONS: The studies had high heterogeneity and offered limited information for hearing loss types and secular trend. CONCLUSIONS AND IMPLICATIONS: Childhood slight or worse hearing loss is prevalent and may be increasing. Advances in understanding hearing loss trajectories, causes, and prevention would require international repositories and longitudinal studies with audiometric data beginning in childhood